The Merit of the Divorced Woman to the Dowry after the Conjugal Right and the Consummation of the Marriage –A Comparative Study between the Islamic Jurisprudence and the Maghreb Family Laws- - Sehailia, Basma; Zazoune, Akli (Journal of Legal Studies and Researches, 2023)
This paper aims at showing the effect of the conjugal right and the consummation of the marriage on the merit of the divorced woman to the full dowry if proven in the Shariaa and the legislations of the Maghreb countries. In addition, it aims at showing the role of the justice in clarifying the meaning of the consummation of the marriage which provide that the consummation of the marriage includes the conjugal right.